2011
DOI: 10.1039/c1cc12491a
|View full text |Cite
|
Sign up to set email alerts
|

Direct assembly synthesis of metal complex–semiconductor hybrid photocatalysts anchored by phosphonate for highly efficient CO2 reduction

Abstract: Hybrid photocatalysts consisting of a ruthenium complex and p-type photoactive N-doped Ta(2)O(5) anchored with an organic group were successfully synthesized by a direct assembly method. The photocatalyst anchored by phosphonate exhibited excellent photoconversion activity of CO(2) to formic acid under visible-light irradiation with respect to the reaction rate and stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 111 publications
(104 citation statements)
references
References 19 publications
2
98
1
3
Order By: Relevance
“…It is recognized to be more efficient for visible light harvesting than cation doping because of the fewer recombination centers formation compared to cation doping [49][50][51][52][53][54][55][56]. Specifically, Zhao et al have prepared N-doped TiO 2 nanotubes (N-TNTs) by hydrothermal method and it is found that because of the substitution of lattice oxygen by N atoms, N-doped TiO 2 shows efficient visible light absorption, and markedly improved visible light photocatalytic activities for CO 2 reduction to yield HCOOH, HCHO, CH 3 OH, etc.…”
Section: Cation or Anion Dopingmentioning
confidence: 99%
“…It is recognized to be more efficient for visible light harvesting than cation doping because of the fewer recombination centers formation compared to cation doping [49][50][51][52][53][54][55][56]. Specifically, Zhao et al have prepared N-doped TiO 2 nanotubes (N-TNTs) by hydrothermal method and it is found that because of the substitution of lattice oxygen by N atoms, N-doped TiO 2 shows efficient visible light absorption, and markedly improved visible light photocatalytic activities for CO 2 reduction to yield HCOOH, HCHO, CH 3 OH, etc.…”
Section: Cation or Anion Dopingmentioning
confidence: 99%
“…11 Preparation of fine Ta 2 O 5 (Ta 2 O 5 -fine) and fine N-doped Ta 2 O 5 (N-Ta 2 O 5 -fine) particles Ta 2 O 5 -fine was prepared using TaCl 5 and ammonia solution as previously reported. 9 N-Ta 2 O 5 -fine was prepared by annealing Ta 2 O 5 -fine under an NH 3 flow at 848 K for 6 h, according to a previously reported method.…”
Section: Synthesis Of Ru-complex [Ru-dpbpy]-n-cmts Hybrid Photocatalystmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] In recent years, the production of transportable fuels such as formic acid or methanol has attracted much attention since these chemicals can act as energy carriers of hydrogen, which outputs a high density of energy after combustion without releasing harmful products. [4][5][6][7][8][9] We have been developing CO 2 fixation systems consisting of a semiconductor and a metal complex workable under visible light. [6][7][8][9] Among the hybrid systems developed, combining Agmodified TaON with a binuclear Ru(II) complex (RuRu' in Chart 1) allows one to convert CO 2 into HCOOH according to a two-step photoexcitation mechanism, as depicted in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%